PRODUCTIVE WAQF MANAGEMENT: CHALLENGES AND OPPORTUNITIES IN ISLAMIC ECONOMIC DEVELOPMENT-A SYSTEMATIC LITERATURE REVIEW - Hesty Gabryella Sirait (SHACRAL: Shari'ah Economics Review Journal, 2024)
Productive waqf has increasingly attracted scholarly and policy attention as a strategic instrument within the Islamic economic system to support sustainable socio-economic development. Unlike traditional waqf practices that primarily focus on religious and social infrastructure, productive waqf emphasizes the optimal utilization of endowed assets to generate continuous economic returns for public welfare. Despite its substantial potential, the implementation of productive waqf remains suboptimal in many Muslim-majority countries, including Indonesia. This study aims to systematically review the existing literature to identify key challenges and opportunities in productive waqf management within the framework of Islamic economics. Employing a qualitative systematic literature review approach, this article synthesizes findings from peer-reviewed journal articles, institutional reports, and policy documents published over the last decade. The review reveals that major challenges include limited managerial capacity of waqf managers (nazhir), weak governance and accountability mechanisms, low public literacy regarding productive waqf, regulatory constraints, and insufficient integration with modern financial systems. Empirical evidence from national institutions indicates a significant gap between the estimated potential of waqf assets and their actual productive utilization. Conversely, the literature highlights several promising opportunities, such as digitalization of waqf collection, collaboration with Islamic financial institutions, professionalization of waqf management, and alignment with Sustainable Development Goals (SDGs). These opportunities position productive waqf as a viable instrument for inclusive economic development, poverty alleviation, and social entrepreneurship. This study contributes to the Islamic economics literature by offering a comprehensive conceptual synthesis of productive waqf management and proposing directions for policy reform and future research to enhance its socio-economic impact.